2021
DOI: 10.1021/acs.est.1c00647
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Patterns and Controls of Nitrous Oxide Concentrations and Fluxes from Urban Inland Waters

Abstract: Inland waters are significant sources of nitrous oxide (N 2 O), a powerful greenhouse gas. However, considerable uncertainty exists in the estimates of N 2 O efflux from global inland waters due to a lack of direct measurements in urban inland waters, which are generally characterized by high carbon and nitrogen concentrations and low carbon-to-nitrogen ratios. Herein, we present direct measurements of N 2 O concentrations and fluxes in lakes and rivers of Beijing, China, during 2018−2020. N 2 O concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 57 publications
1
25
1
Order By: Relevance
“…N 2 O is also the primary cause of stratospheric ozone damage. Its atmospheric concentration has increased from 270 ppb before the industrial revolution to 329 ppb in 2019. Anthropogenic sources contribute an estimated 38.5% (2.7–11.1 Tg N 2 O–N a –1 ) of global N 2 O emissions, 10–17% of which come from inland rivers. , However, compared to the well-documented N 2 O emissions from terrestrial ecosystems, N 2 O emissions from inland rivers have received little attention . Human activities, especially agricultural utilization of synthetic fertilizers and discharge of domestic sewage, have the potential to indirectly enhance N 2 O fluxes from agricultural and urban rivers .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…N 2 O is also the primary cause of stratospheric ozone damage. Its atmospheric concentration has increased from 270 ppb before the industrial revolution to 329 ppb in 2019. Anthropogenic sources contribute an estimated 38.5% (2.7–11.1 Tg N 2 O–N a –1 ) of global N 2 O emissions, 10–17% of which come from inland rivers. , However, compared to the well-documented N 2 O emissions from terrestrial ecosystems, N 2 O emissions from inland rivers have received little attention . Human activities, especially agricultural utilization of synthetic fertilizers and discharge of domestic sewage, have the potential to indirectly enhance N 2 O fluxes from agricultural and urban rivers .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the Intergovernmental Panel on Climate Change (IPCC) used dissolved nitrate and the indirect emission factor (EF 5r ) to estimate the dissolved N 2 O concentration in surface water (i.e., N 2 O–N = NO 3 – –N × EF 5r ) for riverine N 2 O emission estimation. , This IPCC method is convenient for regional and global N 2 O emission estimation as dissolved NO 3 – –N concentration data are more commonly available than N 2 O data. However, the default EF 5r value (0.0026) given by IPCC in 2019 may skew the estimations of riverine N 2 O fluxes with different land use types. , In fact, the EF 5r of freshwater ecosystems remains unspecified, especially for agricultural and urban rivers. ,, The IPCC have refined EF 5r from 0.0075 (1998) to 0.0025 (2006) and to 0.0026 (2019) . Hence, many studies have estimated the EF 5r (EF 5r‑e ) with different landscapes using field-measured dissolved N 2 O and NO 3 – –N concentrations and provide EF 5r‑e for the refinement of the default EF 5r value or the establishment of a regionally-specific EF 5r . ,, Previous studies that investigated the IPCC’s predictions concluded that they only accounted for about 76% of the measured N 2 O emissions in urban rivers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparisons of alternative kinetic rate models (Supporting Information S1) suggest that this relationship reflects a common maximum denitrification rate across sites (μ max term in Equation 3) in contrast to first-order kinetic models used in a number of studies (Gu et al, 2007;Quick et al, 2016;Zarnetske et al, 2011). This approach to maximum denitrification rates is supported by a recent multi-site study of stream denitrification across Beijing, China (Wang et al, 2021). Despite the link between nitrate concentrations and denitrification efficiencies, nitrate was not statistically correlated with N 2 O yields in LINX II experiments.…”
Section: Denitrification Efficiency Controls N 2 O Yieldsmentioning
confidence: 87%
“…where K in is the inhibition constant specified for individual reactions. This modeling framework is supported by a recent large-scale survey of denitrification dynamics across Beijing, China (Wang et al, 2021).…”
Section: Hyporheic Zone Reaction Networkmentioning
confidence: 99%